Fixed Point for Partial Metric Spaces. (6th July 2011) - Mohsenalhosseini, S. A. M.; Mazaheri, H.; Dehghan, M. A.; Zareh, A.
Abstract : We consider the partial metric on a setX, defineϵ -fixed point for maps, and obtain some sufficient and necessary conditions on that, also we obtain some sufficient and necessary theorems onϵ -fixed point.